2008
DOI: 10.1016/j.radonc.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between pretreatment FDG-PET biological target volume and anatomical location of failure after radiation therapy for head and neck cancers

Abstract: Background and Purpose: To assess whether the pretreatment FDG-PET defined biologic target volume (PET-BTV) correlates with the anatomical sites of loco-regional failure (LRF) after RT for head & neck cancer (HNC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 41 publications
3
62
0
1
Order By: Relevance
“…However, we did not find any correlation between the amount (size of the GTV FDG ) or the level (SUV max ) of 18 F-FDG uptake and disease-free survival, although this lack of correlation could be due to the limited number of patients. In fact, whereas the prognostic value of 18 F-FDG PET appears intuitively appealing, recent trials comparing SUV data to disease control in larger patient groups have reported conflicting results (27)(28)(29)(30). In any case, it appears prudent not to use 18 F-FDG PET as the sole instrument for delineating gross tumor volume, since locoregional failures can occur outside the GTV FDG (8,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find any correlation between the amount (size of the GTV FDG ) or the level (SUV max ) of 18 F-FDG uptake and disease-free survival, although this lack of correlation could be due to the limited number of patients. In fact, whereas the prognostic value of 18 F-FDG PET appears intuitively appealing, recent trials comparing SUV data to disease control in larger patient groups have reported conflicting results (27)(28)(29)(30). In any case, it appears prudent not to use 18 F-FDG PET as the sole instrument for delineating gross tumor volume, since locoregional failures can occur outside the GTV FDG (8,30).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, whereas the prognostic value of 18 F-FDG PET appears intuitively appealing, recent trials comparing SUV data to disease control in larger patient groups have reported conflicting results (27)(28)(29)(30). In any case, it appears prudent not to use 18 F-FDG PET as the sole instrument for delineating gross tumor volume, since locoregional failures can occur outside the GTV FDG (8,30). Pathology studies have convincingly demonstrated that no single imaging modality can depict all tumor extensions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the delineation of GTV and standardized uptake value (SUV) levels evaluation allows the design of dose escalation strategies, improving the possibility to identify tumor subvolumes with higher risk of recurrences (17,(47)(48)(49)(50). 18 F-FDG PET may be useful even as a prognostic factor due to the ability to early detect tumor recurrences (15)(16)(17)(18)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…RT has the aim to improve locoregional control both in early stage disease, where RT has an elective role, and in advanced stage, in the setting of combined modality treatment (5). It has been estimated that in the majority of cases, RT treated tumors relapse within the 95% dose coverage volume, probably due to the presence of radiation-resistant hypoxic areas (6)(7)(8)(9)(10)(11)(12).…”
Section: Fdg-pet and Ct-scan Comparison In Gtv Definition For Rt Planmentioning
confidence: 99%
“…This has previously been examined for head and neck patients [34]. Local recurrences were classified as 'infield', 'marginal' or 'out-of-field' if more than 95%, 20-94% and less than 20% of the recurrence volume was within the 95% isodose line [22].…”
Section: Discussionmentioning
confidence: 99%